CONTEMPORARY EUROSCEPTICISM AS A CHALLENGE TO EUROPEAN SOLIDARITY - M. O. Shibkova (Vestnik MGIMO-Universiteta)
The article analyses the influence of Eurosceptic sentiments on the level of solidarity among European Union member states. At the outset of the integration project construction the advantage of the Old Continent unification after being destroyed by the Second World War was apparent. However, with the European Union transformation and the emergence of new challenges, Eurosceptic voices are becoming louder and an increasing number of states start to question the efficiency of supranational institutions and choose to take measures on their own. The main trigger of the rise of Euroscepticism in the new millennium was the financial crisis with austerity measures and citizens' frustration with their low standard of living following. Without taking into consideration the results of the European Parliament Elections 2014, which proved the reinforcement of Eurosceptics, Brussels continued to further develop the integration process. However, with the lapse of time it became clear that Eurosceptics despite being deprived of the right to vote at the supranational level, can implement its potential to influence the EU through their activity within their countries. As a result of their actions the EU is faced up with two serious challenges: Brexit and inability to cope with the migration crisis by common effort. By giving certain examples of the reaction of member states' governments on the migration crisis and illustrating how these actions depend on the extent of Euroscepticism popularity in the countries the author shows that currently the level of European solidarity has become so low that it allows to speak about the transformation of the EU economic crisis into a truly political one.